2016
DOI: 10.1088/1612-2011/13/10/105206
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death and rebirth of entanglement for different dimensional systems driven by a classical random external field

Abstract: The entangled behavior of different dimensional systems driven by classical external random field is investigated. The amount of the survival entanglement between the components of each system is quantified. There are different behaviors of entanglement that come into view decay, sudden death, sudden birth and long-lived entanglement. The maximum entangled states which can be generated from any of theses suggested systems are much fragile than the partially entangled ones. The systems of larger dimensions are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In recent years, open qutrit systems are also concerned and the methods of protecting entanglement in open qubit systems have also been used to the qutrit systems because the latter is superior physical resources than the former in quantum information processing. For instance, the auxiliary quantum qutrits, [ 47 ] the classical driving field, [ 48 ] the weak measurement and the measurement reversal [ 49–52 ] are also effective ways in protecting and regulating entanglement of qutrit systems. In addition, a lot of progress has been made in the experimental implementation of realistic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, open qutrit systems are also concerned and the methods of protecting entanglement in open qubit systems have also been used to the qutrit systems because the latter is superior physical resources than the former in quantum information processing. For instance, the auxiliary quantum qutrits, [ 47 ] the classical driving field, [ 48 ] the weak measurement and the measurement reversal [ 49–52 ] are also effective ways in protecting and regulating entanglement of qutrit systems. In addition, a lot of progress has been made in the experimental implementation of realistic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The transition frequencies from atomic ground state |C⟩ to excited state |A⟩, |B⟩ is 𝜔 A , 𝜔 B , respectively. classical driving field, [48] the weak measurement and the measurement reversal [49][50][51][52] are also effective ways in protecting and regulating entanglement of qutrit systems. In addition, a lot of progress has been made in the experimental implementation of realistic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years a lot of attention has been devoted to the analysis of the combined process, i.e., sudden death, followed by revival of entanglement. These two linked phenomena have been investigated in the case of two qubits interacting with a common reservoir [ 8 , 9 ], trapped atoms or ions under the influence of applied pulses [ 10 ], two cavities interacting with independent reservoirs [ 11 ], quantum systems subjected to a classical random external field [ 12 ], two-level atoms in the presence of a single mode quantized field [ 13 ], dark-soliton qubits [ 14 ], a diamond sample interacting with a solid-state spin bath [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study have shown that CSS goes under spin squeezing sudden death (SSSD) under decoherence except amplitude damping channel. The phenomenon of SSSD is inspired by entanglement sudden death which is widely studied in many physical settings [45][46][47][48][49][50][51][52][53]. So investigations of spin squeezing behaviour under decoherence in CSS motivate us to carry out the study in another symmetric states.…”
Section: Introductionmentioning
confidence: 99%